Job separations and informality in the Russian labor market - Hartmut Lehmann; Tiziano Razzolini; Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2011)
In the years 2003-2008 the Russian economy experienced a period of strong and sustained growth, which was accompanied by large worker turnover and rising informality. We investigate whether the burden of informality falls disproportionately on job separators (displaced workers and quitters) in the Russian labor market in the form of informal employment and undeclared wages in formal jobs. We also pursue the issues whether displaced workers experience more involuntary informal employment than workers who quit and whether informal employment persists. We find a strong positive link between separations and informal employment as well as shares of undeclared wages in formal jobs. Our results also show that displacement entraps some of the workers in involuntary informal employment. Those who quit, in turn, experience voluntary informality for the most part, but there seems a minority of quitting workers who end up in involuntary informal jobs. This scenario does not fall on all separators but predominantly on those with low human capital. Finally, informal employment is indeed persistent since separating from an informal job considerably raises the probability to be informal in the subsequent job.
urn:nbn:de:101:1-201202284995
Keywords: J64; J65; P50; 330; job separations; informality; Russia; Arbeitsmobilität; Schwarzarbeit; Informeller Sektor; Russland